Creative Planning for Library Administration Leadership for the Future, 1st edition - Hendrickson, Kent (Routledge, 2020)
In the seven chapters of this book, first published in 1991, the topics of planning and creativity as they apply to the management of academic libraries are discussed fully, with specific examples and detailed guidelines. Topics such as involving all members of the library staff in decision making and encouraging creativity in an unstable work environment are explored, as are new developments like performance measures.